Phytophilous macroinvertebrate diversity in headwater streams in mountain grasslands in Córdoba, Argentina - Rodriguez, Maria Pia (2017)
Macrophytes play an important role in lotic systems increasing habitat heterogeneity and providing food and shelter for wildlife. The aim of the study was to analyze the structure and composition of the invertebrate community associated with macrophytes in headwater streams in mountain grasslands (Ctalamochita sub-basin, Córdoba, Argentina) in two hydrological periods. The structure of the invertebrate assemblages in different macrophyte species (Hydrocotyle spp., Rorippa nasturtium-aquaticum and Ranunculus flagelliformis) was also evaluated. Three streams were sampled during high water (March 2012) and low water (August 2012) period. In each period, samples of invertebrates associated with the dominant macrophyte in each stream were collected. Seventy-two taxa of phytophilous macroinvertebrates were identified. The most frequent and abundant taxa were Naidinae, Hyalella curvispina, Americabaetis spp., Corynoneura spp. and Rheotanytarsus spp. Assemblages composition differed between hydrological periods and greater abundance of invertebrates was detected in R. nasturtium-aquaticum. The results showed that macrophyte patches in grassland headwater streams harbor an abundant and diverse invertebrate fauna and provide important base information for biomonitoring.